Knowledge about Tuberculosis of Peoples Living in Eastern Part of Nepal - Ghimire, Ram Hari; Ghimire, Sita (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 30-34 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8802